Assessment of seed quality of different commercial lots of PRH 10 produced at different locations - PRAVEEN K. SINGH,; S. S. PARIHAR,; K. K. SINGH,; S. PANDEY,; S. K. YADAV,; Y. SINGH,; A. K. SINGH, (Seed Research, 2026)
Indian Agricultural Research Institute released the world's first superfine grain aromatic rice hybrid PRH10 for commercial cultivation in 2001, which yields 20-25 per cent more than the high yielding Pusa Basmati-1. Farmer's entire crop depends upon the quality of the seed he sows. Hence, it is necessary to check the quality of seeds made available to the farmers. For the present study, twelve commercial seed lots of superfine aromatic rice hybrid Pusa RH10 were collected from ten private seed companies and two public sector undertaking (IARI, New Delhi and IARI-Regional Station, Karnal) located in different agro-climatic zones. All the seed lots were examined for physical purity (i.e. pure seed, inert matter, other crop seed, weed seed, objectionable weed seed and ODV), genetic purity (using grow-out test), germination percentage, seed moisture content and seed health following ISTA rules. Perusal of data revealed that three seed lots were exceeding the prescribed limit of 20 ODV per kg as per Indian Minimum Seed Certification Standards (IMSCS). The pure seed and inert matter varied from 98.8 to 100 per cent and 0.0 to 1.2 per cent respectively, which was within prescribed limit. The other crop seed, objectionable weed and weed seed were not found in any of the seed lots. The 1000 seeds weight varied from 18.59 to 21.30 g. The per cent germination was recorded less than 80 per cent in two seed lots i.e. below the IMSCS. In case of moisture content, one seed lot had higher moisture content (9.95 per cent) than the limit prescribed by IMSCS for moisture proof container. Three seed lots failed to meet the Minimum Standard of genetic purity i.e. 95 per cent. Paddy bunt, the designated disease of rice, was not found in any of the seed lots.